Linear Regression Analysis: The Impact of the Total Population on Halal Certification Applicants in Indonesia (2021-2022) - Risdayani, R; Hidayat, Syamsul; Widodo, Prima Ariyo (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This research investigates the relationship between the total population and the number of halal certification applicants in Indonesia from 2021 to 2022 by employing an applied statistical approach with a focus on the linear regression test. The objective is to discern the extent to which the total population influences the demand for halal certification. The study utilized secondary data collected from various sources and processed through statistical software. The findings reveal a statistically significant relationship between the total population and halal certification applicants, as evidenced by the low significance value (0.001). The regression equation, 49,003-0.000X, indicates a negative correlation, suggesting that as the total population increases, the number of halal certification applicants tends to decrease. The applicative contribution of this research lies in providing valuable insights for policymakers, industries, and halal certifying bodies. Understanding the dynamics of population influence on halal certification demand can guide strategic planning for meeting the growing needs of consumers. However, it is noteworthy that the regression coefficient indicates a nonsignificant contribution of the total population in explaining variations in halal certification applicants, emphasizing the need for additional factors to be considered in comprehensive analyses of halal certification.